THE ROLE-PLAYING LEARNING MODEL IN IMPROVING LANGUAGE LEARNING OUTCOMES - Alva Japa, Hyronimus Edi; admin, admin (Publikasi dan UKI Press UKI Toraja., 2022)
English language learning outcomes using the Role Playing learning model for fifth grade students at SDK ST.Maria Ruteng III. This research is classroom action research (PTK). This classroom action research was carried out in two cycles. Each cycle consisted of 4 stages, namely 1) planning, 2) implementation, 3) observation and 4) reflection. Each cycle I and II was held in 2 meetings. This research was carried out in class VI of SDK ST.Maria Ruteng III, consisting of 30 students. The data in this research was obtained using observation and test methods. The data obtained was analyzed using descriptive statistics. The results of the research showed that the completion of the second cycle of drama playing using the Role Playing learning model for fifth grade students at SDK ST.Maria Ruteng III cycle II was 89.65% or 26 out of 30 students were in the complete category and 10.34% or 4 out of 30 students were in the complete category. incomplete category. Thus, it can be said that the level of achievement of KKM cycle II in drama playing using the Role-Playing learning model has been successful or there has been an increase in language learning outcomes. Indonesia plays drama using the Role Playing learning model for classroom students SDK ST.Maria Ruteng III adapted to the school's KKM.